The correlation between the knowledge level related to practice protocols and dentists’ anxiety levels in practice during the COVID-19 pandemic - Merlya Balbeid; Yuanita Lely Rachmawati; Marchella Anestya Wibowo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: The global epidemic of COVID-19 has reached an emergency status in the health system, including dentistry. The dentist profession is inseparable from the possibility of direct or indirect contact with microorganisms in the patient’s blood or saliva. National and international dental associations, such as Persatuan Dokter Gigi Indonesia and the American Dental Association, have published practice protocols that must be applied by dentists who choose to continue practicing during the COVID-19 pandemic. Dentists’ knowledge of practice protocols in the current situation is very important, as it enables dentists to take infection control measures against virus transmission in the dental practice environment. Strong knowledge can have a positive impact on the psychological state of dentists, such as by reducing the anxiety level of dentists when treating patients during the pandemic. Purpose: To determine the correlation between the level of knowledge of dentists regarding practice protocols and the level of anxiety that they face regarding practicing during the COVID-19 pandemic in Indonesia. Methods: The research design is a correlation analysis, namely research with a cross-sectional approach and purposive sampling, with a total sample of 170 respondents. Data were collected through Google form and univariate analysis was carried out then bivariate analysis with Kendall’s Tau correlation test. Results: This study found that as many as 166 respondents (97.6%) had a good level of knowledge and as many as 87 respondents (51.2%) had a minimum level of anxiety. The results of the analysis were obtained and found to be 0.031, which means p <0.05 so that it shows a relationship between the two variables. Conclusion: There is a correlation between the level of knowledge and the level of anxiety of dentists in practice during the COVID-19 pandemic.